2005
DOI: 10.1117/1.1854679
|View full text |Cite
|
Sign up to set email alerts
|

Broadband reflectance measurements of light penetration, blood oxygenation, hemoglobin concentration, and drug concentration in human intraperitoneal tissues before and after photodynamic therapy

Abstract: We evaluate Photofrin-mediated photodynamic therapy (PDT) in a phase 2 clinical trial as an adjuvant to surgery to treat peritoneal carcinomatosis. We extract tissue optical [reduced scattering (mu(s)'), absorption (mu(a)), and attenuation coefficients (mu(eff))] and physiological [blood oxygen saturation (%S(t)O2), total hemoglobin concentration (THC), and photosensitizer concentration (c(Photofrin))] properties in 12 patients using a diffuse reflectance instrument and algorithms based on the diffusion equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 62 publications
6
103
0
3
Order By: Relevance
“…The effect of light scattering raises questions as to the depth of penetration and absorption and internal activation of light. Absorption sensitivity in regards to light is dependent upon tissue chromospheres such as lipids, water, and photosensitizes [19]. Varying body types in regards to human tissue, amount, thickness, and densities of skin, fat, and fascia, will cause light to penetrate to different depths and will require different frequencies to penetrate tissues [6].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of light scattering raises questions as to the depth of penetration and absorption and internal activation of light. Absorption sensitivity in regards to light is dependent upon tissue chromospheres such as lipids, water, and photosensitizes [19]. Varying body types in regards to human tissue, amount, thickness, and densities of skin, fat, and fascia, will cause light to penetrate to different depths and will require different frequencies to penetrate tissues [6].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in tissue oxygenation due to photochemical oxygen consumption during PDT have been observed directly [65,66], and indirectly through their effect on the photobleaching rate [39,[67][68][69][70]. Recent studies have shown that the concentrations of hemoglobin (Hb), HbO 2 , H 2 O, and photosentizers can be determined from absorption measurements [24,[60][61][62][63]71]. In our current prostate protocol, we accomplish this by repeating the absorption measurements described above, but replacing the laser source with a white light source and the photodiode with a spectrograph.…”
Section: Quantification Of Drug Concentration and Tissue Oxygenationmentioning
confidence: 99%
“…Techniques have been developed to characterize the tissue optical properties and the light fluence rate in vivo [21,22]. Other optical spectroscopic methods [23,24] have been developed to characterize tissue absorption and scattering spectra, which in term provide information about tissue oxygenation and drug concentration. Fluorescence techniques [25,26] can be used to quantify drug concentration and can provide valuable dynamic information relating to the photobleaching of the photosensitizer and oxygen consumption.…”
Section: Introductionmentioning
confidence: 99%
“…[Hb] can be observed in tumor tissue [29,46,67]. The experimental evaluations show that the central prediction function, derived from the average source-detection separation of the probe geometry, should provide enough accuracy to distinguish variations in [Hb] within this range.…”
Section: Discussionmentioning
confidence: 98%
“…This can be achieved easily by calibrating the instrument against a standard or a calibration light source without using an intensity- [53,67]. The [Hb] in colon was found to be 0.601 g/dL [46], and was 0.258 g/dL in esophagus [29].…”
Section: Discussionmentioning
confidence: 99%